Attitudes, weight stigma and misperceptions of weight loss strategies among patients living with obesity in the Lazio Region, Italy - Colangeli, Luca; Russo, Benedetta; Capristo, Esmeralda; Mariani, Stefania; Tuccinardi, Dario; Manco, Melania; Scipione, Valeria; Parrotta, Maria Eugenia; Capoccia, Danila; Guglielmi, Valeria (Frontiers in Endocrinology, 2024)
Introduction Patient engagement is essential to achieve long-term goals in obesity management. It is crucial to identify patients’ perspectives, misperceptions and unmet educational needs on obesity etiology and treatments, to establish a correct therapeutic alliance between healthcare providers and patients. Methods Objective: This study, promoted by the regional section of the Italian Obesity Society (SIO Lazio), explores attitudes towards obesity, self-awareness, misperceptions of weight loss strategies, experiences of weight stigma and educational needs of patients living with overweight or obesity. Design and subject: We conducted an anonymous survey among patients who accessed an Obesity Management Centers across the Lazio region of Italy for the first time, from October 2023 to April 2024. Approach: The survey consisted of 27 closed-ended questions grouped into 4 sections: (1) sociodemographic factors and self-reported anthropometric measures; (2) self-awareness and attitudes towards obesity and weight loss strategies; (3) experiences of obesity-related stigma; (4) knowledge and perceptions of obesity treatment options. Results A total of 300 patients (67.9% women, aged 49.1 ± 14.4 years) returned completed surveys. Despite the self-reported BMI 35.3 ± 7.0 kg/m2 with three out of four (75.3%) of participants having a BMI ≥ 30 kg/m2, only 49% correctly identified themselves as affected by obesity. Almost one-third of the patients believed that obesity does not imply a genetic predisposition (31.9%) and that it is always secondary to psychological or behavioral disorders (29.7%). Interestingly, 66.7% of the patients declared themselves as completely responsible for their own condition and 39.4% considered obesity always treatable by means of lifestyle interventions. Stigma and weight discrimination in healthcare settings were reported by a substantial portion of patients (31.9%). A perception of inadequate support from the National Healthcare System emerged in most of the interviews (61.9%). Most patients (72.1%) felt they were not sufficiently informed about anti-obesity medications and a relevant part of their knowledge was derived from healthcare providers (57.7%) and social networks (19.1%). Weight loss medications were considered useful (63.2%) or necessary (18.4%) by the majority of patients, but only 60.1% would accept without any hesitation a pharmacologic treatment. The main reasons for refusal of pharmacological treatments were the belief that lifestyle intervention is a sufficient treatment (46.9%), the fear of adverse effects (28.1%) and feeling defeated (12.5%). Similarly, for most of participants bariatric surgery is useful (73.3%) or necessary (13.6%). Conclusion Despite advancements in obesity research, this study underscores the need to improve patient education and public awareness to optimize the management and treatment of obesity. Addressing misconceptions, stigma, and gaps in knowledge are critical steps towards improving patient outcomes and fostering a supportive healthcare environment.